Use of Cervical Cancer Screening among Patients of Primary Healthcare Services: Northeast Portugal - Cristina Teixeira; Celeste Antão; Eugénia Anes; Maria José Gomes; Ana Versos; Conceição Tomé (Karger Publishers, 2022)
Background: Understanding the overuse and underuse of cervical cancer (CC) screening plays a role in preventing such behaviours, allowing to maximize the CC screening uptake. Aim: To assess the predictors of being over-screened and never/under-screened in CC screening in Northeast Portugal. Methods: This is a part of a larger cross-sectional survey carried out in two public health centres in Northeast Portugal (October 2017 to June 2018). Data collection was based on a face-to-face interview. This analysis included 764 women (aged 25-60 years) classified according to the use of CC screening into guideline-consistent screened, over-screened and unscreened/under-screened. Multivariate logistic regression models were conducted to assess predictors of being over-screened and never/under-screened. Adjusted odds ratio (OR) and respective 95% confidence interval (95% CI) were obtained. Results: One-fourth (n = 197) of participants were unscreened/under-screened and 50.0% (n = 382) of them were classified as over-screened. Regular visits with primary care physicians (OR = 0.44; 95% CI: 0.26-0.76) and higher age (OR = 0.98; 95% CI: 0.96-1.00) reduced the odds of being unscreened/under-screened. Women who received prescription/recommendation for CC screening from primary care physician (OR = 1.89; 95% CI: 1.09-3.29) or both primary care physician and nurse (OR = 2.62; 95% CI: 1.10-6.22) were more likely to be over-screened. Higher level of CC health literacy decreases the odds of being over-screened (OR = 0.95; 95% CI: 0.90-1.00) and unscreened/under-screened (OR = 0.87; 95% CI: 0.82-0.92). The majority of over-screened (52.2%) and of under-screened (44.2%) women reported that their screening frequency was based on healthcare provider prescription. Among never-screened women, 60.2% reported that no one prescribed screening. Conclusion: The increase in CC health literacy can maximize CC screening uptake. Primary healthcare providers could play a role in preventing the overuse and underuse of CC screening.